A COMPARATIVE INTERPRETATION OF LEXICAL AND PROPOSITIVE NOMINATIONS - Mardonovna, Suleymanova N. (Journal of Language and Literature, 2017)
The central unit of the language is the nominative meaning of the word, which has been thoroughly studied by the present time of the development of the linguistic science and had fundamental research in this area. However, the study of the nominative meaning of syntactic structures in recent years has also begun to be included in the research agenda, and today it has become a special syntactic problem. It is noteworthy that syntactic structures, in particular, the nominative character of the word, show that there is a significant difference between the nominative features of the word and a sentence. Firstly, a word is literally a nominative unit, and therefore maintains its status in the speech and in the vocabulary of the language. The sentence is temporal in this aspect. It can only express a real nominative meaning when used in speech. Secondly, the fact that the word is a nominative unity is also clearly seen in the context of the denotation, which is reflected in the form of a specific narrative expressed through it. In other words, the expression of the word (signifier) is a pure sign, and the expression of the statement is a sign that also comes in the status of a denotation. Thirdly, the word is often polysemantic, and the sentence is monosemantic. Fourthly, if the word is a nominative unit, then this is the case once in a lifetime.